Development of profit-based unit commitment solution using particle swarm optimization / Ida Syahirah Baderol Iskandar - Baderol Iskandar, Ida Syahirah (2017)
This thesis presents the solution of profit-based unit commitment (PBUC) by using particle swarm optimization (PSO) technique. In this study, the on/off scheduling of generator units will be determined based on maximizing the profit while fulfilling the constraints. The proposed solution also helps to make decision on how much power and reserve is put up in the market sale while giving maximum profit based on the price behavior in the spot market. This optimization technique is performed on a test system consisting of three and ten generating units to study the effectiveness of this method to the PBUC problems. The results are compared to conventional unit commitment problem (UCP).